THE EFFECT OF PALM OIL’S PROTECTION COSTS ON COMPANY REVENEW - Anas Josua Sihombing; Ardilla; Tifany Zia Aznur; Rahmad Dian; Febriana Roosmawati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
This study aims to determine the cost of controlling pests of fire caterpillars (Setothosea asigna) and bag caterpillars (Metisa plana) of oil palm producing plants and analyze the effect of the cost of controlling pests of fire caterpillars (Setothosea asigna) and bag caterpillars ( Metisa plana) of oil palm producing plants on the income of Kebun Bah Jambi PT. Perkebunan Nusantara IV. This study uses quantitative methods using simple linear regression analysis techniques with the help of the SPSS program. The sample in this study is the last 3 years of pest control data and the last 3 years of palm oil production data. The results of the study can be concluded: the regression equation Y = 2.617E11 - 1021.130X, meaning that the effect of variable X (pest control) on variable Y (income) is negative. The elasticity value of pest control in this study is 1021.130. This shows that each additional cost of pest control of Rp. 1, the company's revenue decreases by Rp. 1,021.13. The coefficient value obtained (R2) is 0.847, meaning that pest control costs affect revenue by 84.7%, while the remaining 15.3% is influenced by other variables not included in this study.